Anion-doped graphene-loaded 3d transition metal catalyst, ceramic-based spherical catalyst, and preparation method and application of anion-doped graphene-loaded 3d transition metal catalyst

By doping 3d transition metal precursors and organic complexing agents on graphene oxide, the electronic structure of metal sites is regulated and metal crystallization is inhibited, and the problem of easy crystallization of the catalyst during calcination is solved, achieving high catalytic activity and simple preparation method effects.

CN119680594APending Publication Date: 2025-03-25JIANGSU ECOLOGICAL ENVIRONMENT TECHNOLOGY RESEARCH INSTITUTE CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411937872.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, catalysts containing transition metals are prone to crystallization during calcination, resulting in poor catalytic performance.

Method used

By doping 3d transition metal precursors and organic complexing agents on graphene oxide, the electronic structure of metal sites is regulated and the crystallization behavior of metals during high-temperature calcination is inhibited, thereby preparing anion-doped graphene-supported 3d transition metal catalyst.

Benefits of technology

The prepared catalyst has low metal crystallinity, high catalytic activity for advanced ozone oxidation reactions, and simple preparation method, which is convenient for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680594A_ABST
    Figure CN119680594A_ABST
Patent Text Reader

Abstract

The invention discloses an anion-doped graphene-loaded 3d transition metal catalyst, a ceramic-based spherical particle catalyst, a preparation method and an application of the anion-doped graphene-loaded 3d transition metal catalyst and the ceramic-based spherical particle catalyst. The preparation method of the anion-doped graphene loaded 3d transition metal catalyst comprises the following steps: uniformly mixing a mixed solution containing graphene oxide, a 3d transition metal precursor and an organic complexing agent, and sequentially carrying out solid-liquid separation, drying and calcining to obtain the anion-doped graphene loaded 3d transition metal catalyst, the mass ratio of the graphene oxide to the 3d transition metal precursor is 1: (0.65 to 2.5), and the calcining temperature is 550 to 950 DEG C. The catalyst prepared by the invention is low in metal crystallinity and has high catalytic activity on ozone advanced oxidation reaction; the preparation method is simple, convenient to operate and beneficial to large-scale production; the synthesized ceramic-based spherical catalyst can be recycled and has a relatively high commercial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to an anion-doped graphene-loaded 3d transition metal catalyst, a ceramic-based pellet catalyst, and a preparation method and application thereof. Background Art

[0002] Since it was proposed in the 1980s, the advanced oxidation process has been considered one of the most effective methods for removing organic pollutants. Through the activation of oxidants such as H2O2, O3, and persulfate by catalysts to produce highly oxidizing active oxygen free radicals, advanced oxidation can quickly and indiscriminately degrade large molecular refractory organic pollutants into harmless or low-toxic small molecular pollutants, or even completely mineralize them into CO2 and H2O. As the core component of the advanced oxidation reaction equipment, the catalyst determines the reaction rate. The traditional advanced catalytic oxidation process uses metal ions as catalysts and reacts in a homogeneous solution, but there are disadvantages such as a narrow pH working range and easy hydrolysis of metal ions. Therefore, the development of heterogeneous catalysts has attracted more and more attention.

[0003] In order to improve the stability of carbon-based catalysts, calcination treatment is often required during the preparation process. By introducing heteroatoms during the preparation process, a more flexible coordination mode can be introduced, the electronic structure of the metal site can be optimized, and the charge transfer between the active site and the intermediate can be accelerated. Chinese patent CN 113559912B discloses a nitrogen-sulfur co-doped graphene-supported cobalt catalyst, which uses urea and sublimated sulfur as nitrogen sources and sulfur sources to prepare nitrogen-sulfur co-doped graphene-supported cobalt catalysts, which have good performance for catalyzing persulfate degradation of tetracycline, but the crystalline cobalt sulfur compound in the catalyst prepared by it has a high crystallinity, and the metal Co agglomerates, and only a layer of metal sites on the metal surface can play a catalytic effect, while the internal metal atoms cannot be exposed and cannot play a role, resulting in low catalyst atom utilization. Therefore, how to develop a catalyst that can inhibit the crystallization behavior of metals during high-temperature calcination and has excellent catalytic performance is a problem to be solved urgently. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the defects of the catalyst containing transition metal in the prior art that the metal is easy to crystallize and the catalytic performance is poor during the calcination process, and to provide an anion-doped graphene-supported 3d transition metal catalyst, a ceramic-based pellet catalyst, and a preparation method and application. The catalyst prepared by the present invention has low metal crystallinity and high catalytic activity for ozone advanced oxidation reaction; the preparation method is simple, easy to operate, and conducive to large-scale production; the synthesized ceramic-based pellet catalyst can be repeatedly recycled and has a high commercial application prospect.

[0005] The present invention uses graphene oxide, a 3d transition metal precursor and an organic complexing agent as raw materials to prepare an anion-doped graphene-supported 3d transition metal catalyst. By complexing sulfur-containing, phosphorus-containing and nitrogen-containing organic matter with a specific type of 3d transition metal and matching a specific mass ratio of graphene oxide and the 3d transition metal precursor, as well as a calcination temperature, the electronic structure of the metal site is regulated and the crystallization behavior of the metal during high-temperature calcination is inhibited, thereby improving the ozone advanced oxidation performance of the graphene-supported 3d transition metal catalyst. Furthermore, by soaking ceramic-based pellets in a mixed solution containing graphene oxide, the 3d transition metal precursor and the organic complexing agent and then calcining, a ceramic-based pellet catalyst is prepared. The ceramic-based pellet catalyst not only has high catalytic activity for ozone advanced oxidation reaction, but also can be repeatedly recycled, thereby greatly improving economic benefits.

[0006] The present invention solves the above technical problems through the following technical solutions: The present invention provides a method for preparing an anion-doped graphene-supported 3d transition metal catalyst, comprising the following steps: The mixed solution containing graphene oxide, 3d transition metal precursor and organic complexing agent is uniformly mixed, and then solid-liquid separation, drying and calcination are carried out in sequence to obtain the anion-doped graphene-supported 3d transition metal catalyst; the mass ratio of the graphene oxide to the 3d transition metal precursor is 1: (0.65-2.5), and the calcination temperature is 550-950°C; Option 1: When the 3d transition metal precursor includes a Co metal precursor and the mass percentage of the Co metal precursor is the highest, the organic complexing agent is a phosphorus- and / or sulfur-containing organic molecule having coordination ability for the 3d transition metal; Option 2: When the 3d transition metal precursor includes an Fe metal precursor and the Fe metal precursor has the highest mass percentage, the organic complexing agent is an organic molecule containing one or more of phosphorus, sulfur and nitrogen that has coordination ability for the 3d transition metal; Option 3: When the 3d transition metal precursor includes Mn and / or Ni metal precursor and the mass percentage of the Mn and / or Ni metal precursor is the highest, the organic complexing agent is a nitrogen-containing organic molecule having coordination ability for the 3d transition metal; Option 4: When the 3d transition metal precursor includes any two or more of Co, Fe, Mn and Ni metal precursors and the metal precursor species with the highest mass percentage are two or more at the same time, the organic complexing agent is an organic molecule containing one or more of phosphorus, sulfur and nitrogen that has coordination ability for the 3d transition metal; The mass percentage refers to the percentage of the mass of each metal precursor to the total mass of the 3d transition metal precursor.

[0007] In the present invention, the graphene oxide is generally industrial-grade graphene. The number of layers of the graphene oxide is preferably less than 10 layers, more preferably 5-10 layers. The specific surface area of ​​the graphene oxide is preferably 20-200 m 2 / g.

[0008] In the present invention, the 3d transition metal precursor is preferably one or more of the hydrochloride, nitrate, sulfate, acetate and acetylacetonate of the 3d transition metal.

[0009] In the present invention, the Co metal precursor may be one or more of cobalt chloride, cobalt sulfate and cobalt nitrate.

[0010] In the present invention, the Fe metal precursor may be ferrous chloride and / or ferrous sulfate.

[0011] In the present invention, the Mn metal precursor may be one or more of manganese chloride, manganese sulfate and manganese nitrate.

[0012] In the present invention, the Ni metal precursor may be one or more of nickel chloride, nickel sulfate and nickel nitrate.

[0013] In the present invention, the phosphorus-containing organic molecule is preferably one or more of phytic acid, nucleotide and phosphate.

[0014] In the present invention, the nitrogen-containing organic molecule is preferably one or more of amino acids, nucleotides, methionine and urea. The amino acid is, for example, histidine.

[0015] In the present invention, the sulfur-containing organic molecule is preferably one or more of sodium hexadecylbenzenesulfonate, methionine, thiophenol and mercaptan.

[0016] In the present invention, the mass ratio of the graphene oxide to the 3d transition metal precursor is preferably 1:(0.8-2), such as 1:0.8, 1:1, 1:1.2, 1:1.5 or 1:2.

[0017] In the present invention, the mass ratio of the 3d transition metal precursor to the organic complexing agent may be 1:(0.3-3), preferably 1:(0.5-2), for example 1:1.

[0018] In the present invention, the solvent in the mixed solution can be conventional in the art, and is generally deionized water.

[0019] In the present invention, the concentration of graphene oxide in the mixed solution may be (0.05-0.3) g / mL, such as 0.1 g / mL or 0.2 g / mL.

[0020] In scheme 1, the organic complexing agent is preferably a phosphorus- and / or sulfur-containing, nitrogen-free organic molecule that has coordination ability for 3d transition metals.

[0021] In scheme 1, in certain preferred embodiments, the 3d transition metal precursor is a Co metal precursor, and the organic complexing agent is phytic acid or sodium hexadecylbenzenesulfonate.

[0022] In a specific embodiment, the 3d transition metal precursor is cobalt chloride, and the organic complexing agent is phytic acid or sodium hexadecylbenzenesulfonate.

[0023] In scheme 1, when the 3d transition metal precursor also includes one or more of an Fe metal precursor, a Ni metal precursor and a Mn metal precursor, the ratio of the mass of the Co metal precursor to the total mass of the 3d transition metal precursor is preferably (0.55-0.8):1, for example 0.67:1.

[0024] In scheme 1, in certain preferred embodiments, the 3d transition metal precursor is a Co metal precursor and a Fe metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Fe metal precursor is 2:1.

[0025] In scheme 1, in certain preferred embodiments, the 3d transition metal precursor is a Co metal precursor and a Ni metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Ni metal precursor is 2:1.

[0026] In scheme 1, in certain preferred embodiments, the 3d transition metal precursor is a Co metal precursor and a Mn metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Mn metal precursor is 2:1.

[0027] In Scheme 2, in certain preferred embodiments, the 3d transition metal precursor is an Fe metal precursor, and the organic complexing agent is sodium hexadecylbenzenesulfonate.

[0028] In a specific embodiment, the 3d transition metal precursor is ferrous chloride, and the organic complexing agent is sodium hexadecylbenzenesulfonate.

[0029] In Scheme 2, in certain preferred embodiments, the 3d transition metal precursor is an Fe metal precursor, and the organic complexing agent is histidine.

[0030] In Option 2, when the 3d transition metal precursor also includes one or more of a Co metal precursor, a Ni metal precursor and a Mn metal precursor, the ratio of the mass of the Fe metal precursor to the total mass of the 3d transition metal precursor is preferably (0.55-0.8):1, for example 0.67:1.

[0031] In Scheme 2, in certain preferred embodiments, the 3d transition metal precursor is a Fe metal precursor and a Co metal precursor, the organic complexing agent is sodium hexadecyl sulfonate, and the mass ratio of the Fe metal precursor to the Co metal precursor is 2:1.

[0032] In Scheme 2, in certain preferred embodiments, the 3d transition metal precursor is an Fe metal precursor and a Ni metal precursor, the organic complexing agent is sodium hexadecyl sulfonate, and the mass ratio of the Fe metal precursor to the Ni metal precursor is 2:1.

[0033] In Scheme 2, in certain preferred embodiments, the 3d transition metal precursor is a Fe metal precursor and a Mn metal precursor, the organic complexing agent is sodium hexadecyl sulfonate, and the mass ratio of the Fe metal precursor to the Mn metal precursor is 2:1.

[0034] In scheme three, the organic complexing agent is preferably an organic molecule containing nitrogen and not containing phosphorus and sulfur that has coordination ability for 3d transition metals.

[0035] In Scheme 3, in certain preferred embodiments, the 3d transition metal precursor is a Mn metal precursor, and the organic complexing agent is histidine.

[0036] In a specific embodiment, the 3d transition metal precursor is manganese chloride, and the organic complexing agent is histidine.

[0037] In scheme three, in certain preferred embodiments, the 3d transition metal precursor is a Ni metal precursor, and the organic chelating agent is histidine.

[0038] In a specific embodiment, the 3d transition metal precursor is nickel chloride, and the organic complexing agent is histidine.

[0039] In scheme 4, in certain preferred embodiments, the 3d transition metal precursor is a Co metal precursor and a Fe metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Fe metal precursor is 1:1; Or, the 3d transition metal precursor is a Co metal precursor and a Ni metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Ni metal precursor is preferably 1:1; Alternatively, the 3d transition metal precursor is a Co metal precursor and a Mn metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Mn metal precursor is preferably 1:1.

[0040] In Scheme 4, in a specific implementation scheme, the 3d transition metal precursors are cobalt chloride and ferric chloride, the organic complexing agent is phytic acid, and the mass ratio of the cobalt chloride to the ferric chloride is 1:1.

[0041] In the present invention, the mixing method can be conventional in the art, such as stirring, ultrasound or shaking. The mixing time can be 10-30 minutes, such as 20 minutes.

[0042] In the present invention, the solid-liquid separation method can be conventional in the art, such as centrifugation, filtration or suction filtration. The centrifugal speed can be 3000-6000rpm, such as 5000rpm. The centrifugal time can be 3-5min.

[0043] In the present invention, the drying method may be conventional in the art, such as drying. The drying temperature may be 60-90° C., such as 65° C. The drying time may be 6-24 h, such as 12 h.

[0044] In the present invention, according to the common practice in the art, grinding is generally required before calcination.

[0045] In the present invention, according to the common practice in the art, the calcination is generally performed in an inert gas atmosphere, such as nitrogen or argon.

[0046] In the present invention, the calcination temperature is preferably 600-900°C, such as 600°C, 650°C, 700°C, 800°C, 850°C or 900°C.

[0047] In the present invention, the calcination time is preferably 0.5-3 h, such as 1 h or 2 h.

[0048] In the present invention, the rate of heating to the calcination temperature may be 2-10° C. / min, for example 5° C. / min.

[0049] In the present invention, according to the conventional art, washing and drying are generally required after the calcination. The solvent used in the washing process can be one or more of deionized water, methanol and ethanol.

[0050] The present invention also provides an anion-doped graphene-loaded 3d transition metal catalyst prepared by the above-mentioned preparation method.

[0051] The present invention also provides a method for preparing a ceramic-based pelletized catalyst, comprising the following steps: The ceramic-based pellets are immersed in a mixed solution containing graphene oxide, a 3d transition metal precursor and an organic complexing agent, and then sequentially subjected to solid-liquid separation, drying and calcination to obtain the ceramic-based pellet catalyst; the calcination temperature is 550-950° C. The parameter ranges in the mixed solution are as described in the preparation method of the anion-doped graphene-loaded 3d transition metal catalyst.

[0052] In the present invention, in the mixed solution containing graphene oxide, 3d transition metal precursor and organic complexing agent, the types of substances, dosage relationships and solvents are as described in the preparation method of the anion-doped graphene-supported 3d transition metal catalyst, and will not be repeated here.

[0053] In the present invention, the ceramic-based pellets preferably include one or more of ceramsite, alumina pellets, molecular sieve pellets and artificial zeolite pellets.

[0054] In the present invention, the liquid surface of the mixed solution can generally just cover the ceramic-based pellets. The ratio of the volume of the mixed solution to the mass of the ceramic-based pellets is generally not less than 1 mL / g, preferably 1: (1-20) mL / g, such as 1 mL / g. The mass ratio of the graphene oxide to the ceramic-based pellets is preferably 1: (2-30), more preferably 1: (5-20), such as 1: 8, 1: 10, 1: 15 or 1: 20. According to the convention in the art, the mixed solution can be repeatedly soaked and used, and can generally be reused 7-10 times.

[0055] In the present invention, the soaking time may be 5-20 minutes, for example 10 minutes. The soaking is generally performed in a static state.

[0056] In the present invention, the solid-liquid separation method can be conventional in the art, such as centrifugation, filtration or decanting.

[0057] In the present invention, the drying method may be conventional in the art, such as drying. The drying temperature may be 60-90° C., such as 65° C. The drying time may be 6-24 h, such as 12 h.

[0058] In the present invention, the calcination temperature is preferably 600-900°C, such as 600°C, 650°C, 700°C, 800°C, 850°C or 900°C. The calcination time is preferably 0.5-3h, such as 1h or 2h. The rate of heating to the calcination temperature can be 2-10°C / min, such as 5°C / min.

[0059] The present invention also provides a ceramic-based pellet catalyst prepared by the above-mentioned preparation method.

[0060] The present invention also provides an application of the anion-doped graphene-loaded 3d transition metal catalyst as described above or the ceramic-based pellet catalyst as described above in the field of sewage degradation.

[0061] In the present invention, the anion-doped graphene-supported 3d transition metal catalyst as described above or the ceramic-based pellet catalyst as described above is preferably used in the ozone advanced oxidation reaction.

[0062] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0063] The reagents and raw materials used in the present invention are commercially available.

[0064] The positive and progressive effects of the present invention are: The catalyst metal prepared by the present invention has low crystallinity and high catalytic activity for ozone advanced oxidation reaction; the preparation method is simple, easy to operate, and conducive to large-scale production; the synthesized ceramic-based pellet catalyst not only has high catalytic activity, but can also be repeatedly recycled and has high commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is a physical photo of the product Co-P / G obtained in Example 1; Figure 2 This is the SEM image of the product Co-P / G obtained in Example 1; Figure 3 Part (a) is the elemental distribution diagram of the product Co-P / G obtained in Example 1; Figure 3 Part (b) is the EDX spectrum of the product Co-P / G obtained in Example 1; Figure 4 The XRD patterns of the product Co-P / G obtained in Example 1, the product Co / G obtained in Comparative Example 2, and the precursor graphene oxide powder; Figure 5 Part (a) is the ceramsite before being soaked in the mixed solution; Figure 5 Part (b) is the calcined ceramsite prepared in Example 12; Figure 6 The product Co-P / G obtained in Example 1, the precursor graphene oxide powder, and the COD reduction ratio over time without adding any catalyst; Figure 7 This is a graph showing the COD reduction ratio and quality change of the Co-P / G prepared in Example 1 after five cycles; Figure 8 Part (a) is a graph showing the degradation rate of bisphenol A by Co-P / G prepared in Example 1 under different pH environments; Figure 8Part (b) is a graph showing the degradation rate of Co-P / G prepared in Example 1 for different simulated pollutants. DETAILED DESCRIPTION

[0066] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0067] The raw material information used in the following examples and comparative examples is as follows: Graphene oxide was purchased from Hangzhuo Metal Materials (Taobao), particle size D 50 : 7-10 microns, number of layers: 5-10 layers, specific surface area: 50-200 m 2 / g, thickness: <100nm, carbon content: >95%.

[0068] Ceramic granules were purchased from Yuying Environmental Protection Building Materials Factory (Taobao), with a particle size of 3-5 mm, porosity of 55-58%, and bulk density of 0.7-1.2 g / cm 3 ; Sodium hydroxide content %: ≤1.50.

[0069] Alumina pellets were purchased from Hongyun Environmental Protection (Taobao), particle size: 3-5mm, bulk density: 750kg- / m 3 ; 3A molecular sieve pellets were purchased from Hongyun Environmental Protection (Taobao), particle size: 3-5mm, bulk density: 680kg- / m 3 , water absorption ≥80%WT.

[0070] Artificial zeolite pellets were purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd., with a particle size of 3-5 mm, ignition loss of 15-30%, and soluble salt ≤1.50%. Example 1

[0071] 5 g of graphene oxide powder, 6 g of cobalt chloride, and 6 g of phytic acid were dispersed in 50 ml of aqueous solution and magnetically stirred for 20 minutes; centrifuged at 5000 rpm for 3 minutes, the supernatant was poured off, and the solid precipitate obtained after centrifugation was placed in a blast oven and dried at 65°C for 12 hours; after grinding and drying, it was transferred to a porcelain boat and placed in a tube furnace for high-temperature calcination under a nitrogen atmosphere, and the temperature was increased to 800°C at a heating rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, the sample was taken out, washed with deionized water, and dried again to obtain graphene-loaded cobalt-phosphorus composite nanosheets (Co-P / G). Example 2

[0072] Compared with Example 1, except that the calcination temperature is adjusted to 600° C., the other operations and conditions are the same as those of Example 1. Example 3

[0073] Compared with Example 1, except that the calcination temperature is adjusted to 900° C., the other operations and conditions are the same as those of Example 1. Example 4

[0074] Compared with Example 1, except that the addition amount of cobalt chloride is adjusted to 4 grams and the addition amount of phytic acid is adjusted to 4 grams, the other operations and conditions are the same as those of Example 1. Example 5

[0075] Compared with Example 1, except that the addition amount of cobalt chloride is adjusted to 10 grams and the addition amount of phytic acid is adjusted to 10 grams, the other operations and conditions are the same as those of Example 1. Example 6

[0076] Compared with Example 1, except that phytic acid is replaced by sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those of Example 1. Example 7

[0077] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of ferrous chloride, the other operations and conditions are the same as those of Example 1. Example 8

[0078] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of ferrous chloride, and 6 grams of phytic acid is replaced by 6 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those of Example 1. Example 9

[0079] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of ferrous chloride, and 6 grams of phytic acid is replaced by 6 grams of histidine, the other operations and conditions are the same as those of Example 1. Example 10

[0080] Compared with Example 1, except that 6 grams of cobalt chloride was replaced by 6 grams of manganese chloride, and 6 grams of phytic acid was replaced by 6 grams of histidine, the other operations and conditions were the same as those in Example 1. Embodiment 11

[0081] Compared with Example 1, except that 6 grams of cobalt chloride was replaced by 6 grams of nickel chloride, and 6 grams of phytic acid was replaced by 6 grams of histidine, the other operations and conditions were the same as those in Example 1. Example 12

[0082] 20 grams of graphene oxide powder, 24 grams of cobalt chloride, and 24 grams of phytic acid were dispersed in 200 milliliters of aqueous solution. After magnetic stirring for 20 minutes, 200 grams of ceramsite were added, soaked for 10 minutes, and the solution was poured off. The wet ceramsite was placed in a blast oven and dried at 65°C for 12 hours. The dried ceramsite was transferred to a porcelain boat and placed in a tube furnace for high-temperature calcination under a nitrogen atmosphere. The temperature was raised to 800°C at a heating rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, the sample was taken out to obtain graphene-loaded cobalt-sulfur compound-modified ceramsite (Co-P / G). Example 13

[0083] Compared with Example 12, except that 24 grams of phytic acid was replaced by 24 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions were the same as those of Example 12. Embodiment 14

[0084] Compared with Example 12, except that 24 grams of cobalt chloride is replaced by 24 grams of ferrous chloride, and 24 grams of phytic acid is replaced by 24 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those of Example 12. Embodiment 15

[0085] Compared with Example 12, except that 24 grams of cobalt chloride is replaced by 24 grams of manganese chloride, and 24 grams of phytic acid is replaced by 24 grams of histidine, the other operations and conditions are the same as those of Example 12. Example 16

[0086] Compared with Example 12, except that the expanded clay is replaced by alumina pellets, the other operations and conditions are the same as those of Example 12. Embodiment 17

[0087] Compared with Example 12, except that the expanded clay is replaced by molecular sieve pellets, the other operations and conditions are the same as those of Example 12. Embodiment 18

[0088] Compared with Example 12, except that the expanded clay is replaced by artificial zeolite pellets, the other operations and conditions are the same as those of Example 12. Embodiment 19

[0089] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 4 grams of cobalt chloride and 2 grams of ferrous chloride, the other operations and conditions are the same as those in Example 1. Embodiment 20

[0090] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 4 grams of cobalt chloride and 2 grams of nickel chloride, the other operations and conditions are the same as those of Example 1. Embodiment 21

[0091] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 4 grams of cobalt chloride and 2 grams of manganese chloride, the other operations and conditions are the same as those in Example 1. Embodiment 22

[0092] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 3 grams of cobalt chloride and 3 grams of ferrous chloride, the other operations and conditions are the same as those in Example 1. Embodiment 23

[0093] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 3 grams of cobalt chloride and 3 grams of nickel chloride, the other operations and conditions are the same as those of Example 1. Embodiment 24

[0094] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 3 grams of cobalt chloride and 3 grams of manganese chloride, the other operations and conditions are the same as those in Example 1. Embodiment 25

[0095] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 2 grams of cobalt chloride and 4 grams of ferrous chloride, and 6 grams of phytic acid is replaced by 6 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those of Example 1. Embodiment 26

[0096] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 2 grams of nickel chloride and 4 grams of ferrous chloride, and 6 grams of phytic acid is replaced by 6 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those in Example 1. Embodiment 27

[0097] Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 2 grams of manganese chloride and 4 grams of ferrous chloride, and 6 grams of phytic acid is replaced by 6 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those in Example 1.

[0098] Comparative Example 1 Compared with Example 1, except that the calcination temperature is adjusted to 500° C., the other operations and conditions are the same as those of Example 1.

[0099] Comparative Example 2 Compared with Example 1, except that the calcination temperature is adjusted to 1000° C., the other operations and conditions are the same as those of Example 1.

[0100] Comparative Example 3 Compared with Example 1, except that the amount of cobalt chloride added was adjusted to 3 grams, the other operations and conditions were the same as those in Example 1.

[0101] Comparative Example 4 Compared with Example 1, except that the amount of cobalt chloride added was adjusted to 13 g, the other operations and conditions were the same as those in Example 1.

[0102] Comparative Example 5 Compared with Example 1, except that 6 grams of phytic acid was replaced by 6 grams of histidine, the other operations and conditions were the same as those in Example 1.

[0103] Comparative Example 6 Compared with Example 1, except that the complexing agent phytic acid is not added, the other operations and conditions are the same as those of Example 1.

[0104] Comparative Example 7 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of ferrous chloride and the complexing agent phytic acid is not added, the other operations and conditions are the same as those of Example 1.

[0105] Comparative Example 8 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of manganese chloride, the other operations and conditions are the same as those of Example 1.

[0106] Comparative Example 9 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of manganese chloride, and 6 grams of phytic acid is replaced by 6 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those of Example 1.

[0107] Comparative Example 10 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of manganese chloride and the complexing agent phytic acid is not added, the other operations and conditions are the same as those of Example 1.

[0108] Comparative Example 11 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of nickel chloride, the other operations and conditions are the same as those of Example 1.

[0109] Comparative Example 12 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of nickel chloride, and 6 grams of phytic acid is replaced by 6 grams of sodium hexadecylbenzenesulfonate, the other operations and conditions are the same as those of Example 1.

[0110] Comparative Example 13 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 6 grams of nickel chloride and the complexing agent phytic acid is not added, the other operations and conditions are the same as those of Example 1.

[0111] Comparative Example 14 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 2 grams of cobalt chloride and 4 grams of nickel chloride, the other operations and conditions are the same as those of Example 1.

[0112] Comparative Example 15 Compared with Example 1, except that 6 grams of cobalt chloride is replaced by 2 grams of cobalt chloride and 4 grams of manganese chloride, the other operations and conditions are the same as those of Example 1. Effect Example

[0113] (1) Morphology and element content Figure 1 The product Co-P / G obtained in Example 1 is a dark gray powder, and its microstructure is a multilayer nanosheet stacked on top of each other, indicating that the product retains the sheet structure of graphene ( Figure 2 ). According to the element surface distribution map and EDX spectrum analysis, each element is evenly distributed on graphene, and the mass percentage of each element is C 86.5%, O 7.6%, Co 2.9%, P 3.1% ( Figure 3 ).

[0114] Figure 4 It shows that an amorphous or single-atom cobalt-phosphorus complex is formed in the product Co-P / G obtained in Example 1, which is similar to the XRD pattern of the precursor graphene oxide powder. The product Co / G obtained in Comparative Example 6 shows the diffraction peak of cubic phase elemental cobalt, which indicates that without the introduction of a complexing agent, the metal precursor will agglomerate and crystallize during high-temperature calcination, and because graphene, as a carbon material, has reducibility, elemental cobalt is formed. After the introduction of the phytic acid complexing agent, the degree of metal crystallization is significantly reduced, and it is easier to form an amorphous or single-atom cobalt compound.

[0115] Figure 5 It was shown that the color of the ceramsite was significantly deepened after being immersed in the mixed solution and calcined, indicating that its surface was successfully modified by graphene and 3d transition metals.

[0116] (2) Simulated wastewater treatment A series of identical simulated wastewater A was prepared: 1.5 L of 60 mg / L bisphenol A, and 0.2 mL of 30% (mass fraction) hydrogen peroxide was added; Prepare a series of simulated wastewater B with different pH values: 1.5 L of 50 mg / L bisphenol A, add 0.2 mL of 30% (mass fraction) hydrogen peroxide, and adjust the pH value to 5-9 using 1 M nitric acid solution or 1 M sodium hydroxide solution; A series of simulated wastewater C containing different types of organic pollutants were prepared: compared with simulated wastewater A, bisphenol A was replaced by triadimefon, paclobutrazol, diisobutyl phthalate, phenol, and potassium hydrogen phthalate, respectively, and the initial chemical oxygen demand (COD) of the simulated wastewater containing each organic pollutant was controlled to be 120 mg / L; During the test, 2 g of the powdered catalyst prepared in Examples 1-11, Examples 19-27 and Comparative Examples 1-15 were added to 800 ml of simulated wastewater A, and simulated wastewater tests were performed in a washing bottle. 200 g of the modified ceramsite prepared in Examples 12-18 were added to 1.5 liters of simulated wastewater A, and simulated wastewater tests were performed in an aeration tower. Ozone was continuously introduced during the test, with an ozone concentration of 12 mg / L, an air flow rate of 0.5 L / min, and ventilation for 1 hour. According to "HJ 828-2017 Determination of Chemical Oxygen Demand of Water Quality by Dichromate Method", the COD of the simulated wastewater before and after the test was tested.

[0117] Figure 6 It shows that without adding any catalyst, after 1 hour of ozone aeration treatment, the COD reduction ratio is 34.1%. When graphene is added, the COD reduction ratio is 44.2%. Using the product Co-P / G obtained in Example 1 as a catalyst, the COD reduction ratio is 74.7%. This shows that graphene-loaded solid sulfur compounds have good catalytic performance for ozone advanced oxidation. COD reduction ratio = 1-(end COD / initial COD).

[0118] Table 1 shows the catalytic performance of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2 for ozone advanced oxidation reactions, and shows the effect of different calcination temperatures on product performance. Low-temperature calcination leads to incomplete carbonization of organic matter and unstable catalyst structure, while too high a temperature tends to lead to a deeper degree of metal crystallization.

[0119] Table 1 Effect of calcination temperature on the performance of catalysts for ozone degradation of bisphenol A

[0120] Table 2 shows the catalytic performance of the catalysts prepared in Examples 4-5 and Comparative Examples 3-4 for ozone advanced oxidation reaction, indicating that when the metal addition amount is too low, the density of active sites on the graphene surface is reduced and the performance is reduced. When the metal addition amount is too high, on the one hand, the solubility of the metal salt and the complexing agent in water is limited, and on the other hand, too high a metal addition amount is likely to lead to an increase in crystallinity during the calcination process and a decrease in catalytic performance.

[0121] Table 2 Effect of the amount of precursor added on the performance of the catalyst for ozone degradation of bisphenol A

[0122] In addition, the catalyst Co-P / G obtained in Example 1 is structurally stable during the catalyst aeration process, and still has a high degradation rate and mass retention after 5 cycles ( Figure 7 In addition, a series of 2 g of the catalytic oxidation ceramsite prepared in Example 1 were weighed and added to the prepared simulated wastewater B and simulated wastewater C, and the test was carried out according to the above method. The test results are shown in Figure 8 According to the test results, the prepared ceramsite has stable catalytic degradation performance at different pH values ​​and achieves good degradation effects on different organic pollutants.

[0123] Cyclic experiment test process: Test according to the above test process. After each test, filter, wash with deionized water and dry, and replace the simulated wastewater for testing.

[0124] Table 3 shows the catalytic performance of a series of catalysts prepared with cobalt as precursor for ozone advanced oxidation reaction. Among them, the product Co / G obtained in Comparative Example 6, because no complexing agent was added, the metal precursor was crystallized and reduced during the calcination process, and the COD reduction ratio was only 54.3%. According to Example 1, Example 6 and Comparative Example 5, it can be found that phosphorus doping and sulfur doping have the best control on the electronic structure of cobalt, reaching 74.7% and 73.4% respectively, while the catalyst prepared by N doping has poor performance in ozone degradation of bisphenol A.

[0125] Table 3 Performance of graphene-supported cobalt catalysts for ozone degradation of bisphenol A

[0126] Table 4 shows the catalytic performance of a series of catalysts prepared with ferrous chloride as precursor for ozone advanced oxidation reaction. The product Fe / G obtained in Comparative Example 7 catalyzes the degradation of phenol by ozone at 62.4%. The catalytic performances of Examples 7-9 prepared by phosphorus, sulfur and nitrogen doping are 66.5%, 73.2% and 69.5% respectively.

[0127] Table 4 Performance of graphene-supported iron catalysts for ozone degradation of bisphenol A

[0128] Table 5 shows the catalytic performance of a series of catalysts prepared with manganese chloride as a precursor for ozone advanced oxidation reaction. Among them, the highest performance is the nitrogen-doped product Mn-N / G of Example 10, reaching 71.9%. Sulfur and phosphorus doping reduce the catalyst performance, and the catalytic performance of the products of Comparative Examples 8 and 9 are 47.7% and 54.2%, respectively.

[0129] Table 5 Performance of graphene-supported manganese catalysts for ozone degradation of bisphenol A

[0130] Table 6 shows the catalytic performance of a series of catalysts prepared with nickel chloride as a precursor for ozone advanced oxidation reaction. Among them, the highest performance is the nitrogen-doped product Ni-N / G of Example 11, with a catalytic performance of 64.4%, while the performance of the sulfur- and phosphorus-doped catalysts is poor.

[0131] Table 6 Performance of graphene-supported nickel catalysts in ozone degradation of bisphenol A

[0132] Table 7 shows the catalytic performance of the modified ceramsite of Examples 12-15 for ozone advanced oxidation reaction, indicating that each ceramsite catalyst has good performance in catalyzing ozone degradation of bisphenol A. Although ceramsite cannot be dispersed in simulated wastewater, it is easier to separate the catalyst from the wastewater than the powder catalyst, and is therefore more suitable for batch treatment of wastewater in industrial production.

[0133] Table 7 Catalytic performance of ceramsite catalyst in catalytic ozone degradation of bisphenol A

[0134] Table 8 shows the catalytic performance of a series of catalysts prepared with different ceramic materials as substrates for ozone advanced oxidation reaction. From the test results, it can be seen that the ceramic-based pellet catalysts prepared with different ceramic substrates all show excellent catalytic activity.

[0135] Table 8 Performance of ceramic-based pellet catalyst for catalytic ozone degradation of bisphenol A

[0136] Table 9 shows the catalytic performance of a series of catalysts prepared with composite metal precursors for ozone advanced oxidation reactions.

[0137] Table 9 Performance of graphene-supported composite catalysts for ozone degradation of bisphenol A

[0138] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing an anion-doped graphene-supported 3d transition metal catalyst, characterized in that: The steps include: The mixed solution containing graphene oxide, 3d transition metal precursor and organic complexing agent is uniformly mixed, and then solid-liquid separation, drying and calcination are carried out in sequence to obtain the anion-doped graphene-supported 3d transition metal catalyst; the mass ratio of the graphene oxide to the 3d transition metal precursor is 1: (0.65-2.5), and the calcination temperature is 550-950°C; Option 1: When the 3d transition metal precursor includes a Co metal precursor and the mass percentage of the Co metal precursor is the highest, the organic complexing agent is a phosphorus- and / or sulfur-containing organic molecule having coordination ability for the 3d transition metal; Option 2: When the 3d transition metal precursor includes an Fe metal precursor and the Fe metal precursor has the highest mass percentage, the organic complexing agent is an organic molecule containing one or more of phosphorus, sulfur and nitrogen that has coordination ability for the 3d transition metal; Option 3: When the 3d transition metal precursor includes Mn and / or Ni metal precursor and the mass percentage of the Mn and / or Ni metal precursor is the highest, the organic complexing agent is a nitrogen-containing organic molecule having coordination ability for the 3d transition metal; Option 4: When the 3d transition metal precursor includes any two or more of Co, Fe, Mn and Ni metal precursors and the metal precursor species with the highest mass percentage are two or more at the same time, the organic complexing agent is an organic molecule containing one or more of phosphorus, sulfur and nitrogen that has coordination ability for the 3d transition metal; The mass percentage refers to the percentage of the mass of each metal precursor to the total mass of the 3d transition metal precursor.

2. The method for preparing an anion-doped graphene-supported 3d transition metal catalyst according to claim 1, characterized in that: The mixed solution containing graphene oxide, 3d transition metal precursor and organic complexing agent satisfies one or more of the following conditions: (1) The number of layers of the graphene oxide is less than 10; (2) The 3d transition metal precursor is one or more of the hydrochloride, nitrate, sulfate, acetate and acetylacetonate of the 3d transition metal; (3) The Co metal precursor is one or more of cobalt chloride, cobalt sulfate and cobalt nitrate; (4) The Fe metal precursor is ferrous chloride and / or ferrous sulfate; (5) The Mn metal precursor is one or more of manganese chloride, manganese sulfate and manganese nitrate; (6) The Ni metal precursor is one or more of nickel chloride, nickel sulfate and nickel nitrate; (7) The phosphorus-containing organic molecule is one or more of phytic acid, nucleotides and phosphates; (8) The nitrogen-containing organic molecule is one or more of amino acids, nucleotides, methionine and urea; the amino acid is preferably histidine; (9) The sulfur-containing organic molecule is one or more of sodium hexadecylbenzenesulfonate, methionine, thiophenol and thiol.

3. The preparation method of anion-doped graphene-supported 3d transition metal catalyst as claimed in claim 1 or 2, characterized in that, The mixed solution containing graphene oxide, 3d transition metal precursor and organic complexing agent satisfies one or more of the following conditions: (1) The mass ratio of the graphene oxide to the 3d transition metal precursor is 1:(0.8-2), for example, 1:0.8, 1:1, 1:1.2, 1:1.5 or 1:2; (2) The mass ratio of the 3d transition metal precursor to the organic complexing agent is 1:(0.3-3), preferably 1:(0.5-2); (3) The solvent in the mixed solution is deionized water; (4) The concentration of graphene oxide in the mixed solution is (0.05-0.3) g / mL, for example, 0.1 g / mL or 0.2 g / mL.

4. The method for preparing an anion-doped graphene-supported 3d transition metal catalyst according to claim 1 or 2, characterized in that, The mixed solution containing graphene oxide, 3d transition metal precursor and organic complexing agent satisfies one or more of the following conditions: (1) In scheme 1, the organic complexing agent is a phosphorus- and / or sulfur-containing, nitrogen-free organic molecule that has coordination ability for 3d transition metals; (2) In scheme 1, the 3d transition metal precursor is a Co metal precursor, and the organic complexing agent is phytic acid or sodium hexadecylbenzenesulfonate; (3) In scheme 1, when the 3d transition metal precursor further includes one or more of an Fe metal precursor, a Ni metal precursor and a Mn metal precursor, the ratio of the mass of the Co metal precursor to the total mass of the 3d transition metal precursor is (0.55-0.8):1; (4) In scheme 2, the 3d transition metal precursor is an Fe metal precursor, and the organic complexing agent is sodium hexadecylbenzenesulfonate or histidine; (5) In scheme 2, when the 3d transition metal precursor further includes one or more of a Co metal precursor, a Ni metal precursor and a Mn metal precursor, the ratio of the mass of the Fe metal precursor to the total mass of the 3d transition metal precursor is (0.55-0.8):1; (6) In scheme 3, the organic complexing agent is an organic molecule containing nitrogen and not containing phosphorus and sulfur that has coordination ability for 3d transition metal; (7) In scheme 3, the 3d transition metal precursor is a Mn metal precursor or a Ni metal precursor, and the organic complexing agent is histidine; (8) In scheme 4, the 3d transition metal precursor is a Co metal precursor and a Fe metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Fe metal precursor is 1:1; Or, the 3d transition metal precursor is a Co metal precursor and a Ni metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Ni metal precursor is preferably 1:1; Alternatively, the 3d transition metal precursor is a Co metal precursor and a Mn metal precursor, the organic complexing agent is phytic acid, and the mass ratio of the Co metal precursor to the Mn metal precursor is preferably 1:

1.

5. The method for preparing an anion-doped graphene-supported 3d transition metal catalyst according to claim 1 or 2, characterized in that, The preparation method meets one or more of the following conditions: (1) The mixing time is 10-30 minutes; (2) the calcination is carried out in an inert gas atmosphere; (3) The calcination temperature is 600-900°C, for example, 600°C, 650°C, 700°C, 800°C, 850°C or 900°C; (4) The calcination time is 0.5-3 h, for example 1 h or 2 h.

6. The anion-doped graphene-supported 3d transition metal catalyst prepared by the preparation method described in any one of claims 1 to 5.

7. A method for preparing a ceramic-based pelletized catalyst, characterized in that: The steps include: The ceramic-based pellets are immersed in a mixed solution containing graphene oxide, a 3d transition metal precursor and an organic complexing agent as claimed in claim 1, and then subjected to solid-liquid separation, drying and calcination in sequence to obtain the ceramic-based pellet catalyst; the calcination temperature is 550-950°C.

8. The method for preparing a ceramic-based pelletized catalyst according to claim 7, characterized in that: The mixed solution containing graphene oxide, 3d transition metal precursor and organic complexing agent is as described in any one of claims 2 to 4; And / or, the ceramic-based pellets are one or more of ceramsite, alumina pellets, molecular sieve pellets and artificial zeolite pellets.

9. A ceramic-based pellet catalyst obtained by the method for preparing a ceramic-based pellet catalyst according to claim 7 or 8.

10. Use of the anion-doped graphene-supported 3d transition metal catalyst as claimed in claim 6 or the ceramic-based pellet catalyst as claimed in claim 9 in the field of sewage degradation.

Citation Information

Patent Citations

  • Nitrogen-sulfur co-doped graphene-supported cobalt catalysts, their preparation methods and applications

    CN113559912B